2016
DOI: 10.1097/md.0000000000005605
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infection is associated more with drain duration than daily drainage volume in prosthesis-based breast reconstruction

Abstract: In prosthesis-based breast reconstruction, drains are used to prevent seroma formation and to reduce the risk of infection. However, prolonged drainage increases the risk of ascending infection. Although the volume often accepted for drain removal is ≤30 mL per day, the optimal timing to remove the drain for best clinical outcome remains controversial.We did a retrospective cohort study of 569 patients of prosthesis-based breast reconstruction with infection rate as the outcome variable; drain duration and las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 28 publications
3
49
0
2
Order By: Relevance
“…Risk factors identified repeatedly in multivariate analyses using institutional data or the most recent NSQIP data include obesity or increased body mass index (BMI),[38, 6172] larger breast size,[21, 47, 66] diabetes[32, 61, 68, 69, 72, 73] or hyperglycemia,[74] smoking, [16, 42, 61, 6769, 72, 73, 7578] heavy alcohol use,[61, 79] older age,[16, 62, 74, 78], higher ASA score,[57, 69, 79] history of radiotherapy,[21, 42, 64, 77], duration of operation (mastectomy-only),[16, 62, 69], bilateral operation,[21, 68] and drain duration. [47, 80]. In studies that included all operations (with and without immediate reconstruction), implant[68, 77] or autologous flap[68] reconstruction were associated with increased risk of SSI.…”
Section: Risk Factors For Ssi After Breast Surgerymentioning
confidence: 99%
“…Risk factors identified repeatedly in multivariate analyses using institutional data or the most recent NSQIP data include obesity or increased body mass index (BMI),[38, 6172] larger breast size,[21, 47, 66] diabetes[32, 61, 68, 69, 72, 73] or hyperglycemia,[74] smoking, [16, 42, 61, 6769, 72, 73, 7578] heavy alcohol use,[61, 79] older age,[16, 62, 74, 78], higher ASA score,[57, 69, 79] history of radiotherapy,[21, 42, 64, 77], duration of operation (mastectomy-only),[16, 62, 69], bilateral operation,[21, 68] and drain duration. [47, 80]. In studies that included all operations (with and without immediate reconstruction), implant[68, 77] or autologous flap[68] reconstruction were associated with increased risk of SSI.…”
Section: Risk Factors For Ssi After Breast Surgerymentioning
confidence: 99%
“…The low complication profile of immediate breast reconstruction following chemotherapy has been well documented . However, in other surgical fields, chemotherapy has been shown to adversely affect post‐operative outcomes, including delaying wound healing, and increasing susceptibility to infections . Despite this, within post‐mastectomy breast reconstruction, the impact of chemotherapy timing is less well‐characterized and there is a conflict in the literature as to whether timing of chemotherapy increases the risk of complications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found a correlation between drain duration and infections. However, this influence could only be observed for a drain duration of 21 days or longer [33][34][35]. The drain duration of our study population was much shorter (Q1 5 days, Q3 8 days)-therefore, waiting a few more days before removing the drains is unlikely to cause significant more infections.…”
Section: Significance Of Wound Drain Managementmentioning
confidence: 75%